Observation of an excitonic quantum coherence in CdSe nanocrystals - Prezhdo, Oleg V. (2018)
Optical pump-probe spectroscopy with 6-fs pulses elucidates the 1Se1S3/2–1Se2S3/2 excitonic quantum coherence in CdSe nanocrystals. This coherence encodes hole migration over nanometer length scales and markedly alters the displacement amplitudes of coherent phonons.